Registration of Oat Cultivar 'Hayden'. Issue 2 (27th April 2017) - Caffe-Treml, M.; Hall, L.; Bauer, R.; Kleinjan, J.; Hall, N.; Ingemansen, J. A.
Abstract : Despite a significant decrease over the last 50 years, the production of oats ( Avena sativa L.) presents both environmental and health benefits. When incorporated in crop rotations, oat has the potential to improve soil health and to break pest cycles in corn ( Zea mays L.)–soybean [ Glycine max (L.) Merr.] rotations. In addition, the presence of a soluble dietary fiber (β ‐glucan) in oat grain can help prevent cholesterol, coronary heart diseases, and type 2 diabetes. The development of new oat cultivars with superior productivity and high test weight is required to improve the attractiveness of the crop to producers and to maintain or increase oat production in the United States. 'Hayden' (Reg. No. CV‐383, PI 676028) is a spring oat cultivar developed at South Dakota State University and released by the South Dakota Agricultural Experiment Station in 2014. The pedigree of Hayden is 'Buckskin'//ND011054/SD020835. Hayden was developed using a modified bulk and single seed descent selection method. Hayden is a white hulled cultivar with mid‐to‐late maturity. Hayden was evaluated in the South Dakota Crop Performance Testing Oat Variety Trial from 2013 to 2015 and in the Uniform Mid‐Season Oat Performance Nursery in 2013 and 2014 under the experimental number SD111972. Hayden was released because of its excellent yield potential, good yield stability, and high test weight. It is resistant to smut and moderately tolerant to Barley yellow dwarf virus . Hayden also demonstrates good overall milling and nutritional quality.